Strategy (Part I): Conceptual Foundations. Issue 1 (2nd November 2020) - Silver, Kenneth
Abstract: Strategies are mentioned across a variety of domains, from business ethics, to the philosophy of war, philosophy of sport, game theory, and others. However, despite their wide use, very little has been said about how to think about what strategies are or how they relate to other prominently discussed concepts. In this article, I probe the close connection between strategies and plans, which have been much more thoroughly characterized in the philosophy of action. After highlighting the challenges of analyzing strategies in terms of plans, I show how the work done on the connection between plans and intentions can inspire further questions about the nature of strategy. I conclude by showing how one particular innovation in the understanding of plans—how they can be more or less partial—can be used to help us to mark what makes for a good strategy.